How Successful is the Management of Technical and Vocational Institutions, Kuwait, in Reducing Dependence on Expatriates? - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
There is a common perception that technical and vocational education is the ultimate solution for providing industries and business with skilled and semi-skilled manpower. It is considered as a dual type of education system that would allow students to transfer what they have learned in their schools and colleges into real work environment. It is a combination of education that encompasses theory and practice where students spend a certain time in industrial and business premises to acquire the needed knowledge, skills and attitudes. Due to the shortage of skilled and semi-skilled indigenous manpower, the gulf states (e.g., Kuwait, Qatar, United Arab Emirates) have forged technical and vocational education colleges and institutions with the aim to supply essential sectors of their economy (e.g., oil, electricity and water, health sector, infrastructure), with qualified national manpower able to manage, maintain, and adapt the imported technology to suite local environments. However, the success of technical and vocational institution in achieving an acceptable outcome would, to great extent, depend on the quality of the management of technical and vocational institutions. The fact is managing technical and vocational education is completely different from managing a formal education (e.g., formal colleges and universities). This research paper examines how successful is the management of technical and vocational colleges and institutions in providing local industries with indigenous skilled and semi-skilled qualified manpower. The research is based on extensive field work that encompasses a review of the related literature, interviews with sample of heads of supervisors/heads of departments at the Ministry of Health, Ministry of Communications, Ministry of Electricity and Water, and the oil sector in order to assess the quality of graduates from technical and vocational colleges and institutions. Finally, the research will argue that unless the management of technical and vocational colleges and institutions recognize and appreciate the value of building a strong linkage with local industries, its contribution in tackling the shortage of skilled and semi-skilled indigenous in essential sectors on the economy will be below the government expectations, thus continuing relaying on expatriates for years ahead.